STUDI PENERAPAN LESSON STUDY DALAM PENINGKATAN EFEKTIVITAS PRAKTEK PEMBELAJARAN DI MTs NEGERI PRIGEN - wijoyo, Suto (Balai Diklat Keagamaan Surabaya, 2016)
Basically learning is students’ rights. However, there are still a lot ofstudents who do not learn in the classroom. Since a lot of students thatdo not learn, therefore the result of the learning is not maximum inother words the learning is not effective. That’s why one teachers forumis needed to improve the learning to be more effective which is called aslesson study . Concerning with that background above therefore thisresearch aim is: a ) to know the level of achievement of lesson study atMTsN Prigen b ) to know the effectiveness of lesson study in improvingthe learning practice at MTsN Prigen. This research is qualitativedescriptive study. The data collected by observation and interview wasanalyzed by using percentage and score. From the result and dataanalysis it is concluded that: a ) lesson study at MTs Prigen was ‘ goodenough ‘implemented b ) the implementation of t lesson study at MTsNPrigen can improve the effectiveness of learning practice.